FINANCIAL PERFORMANCE IN THE DIGITAL ERA: A SYSTEMATIC LITERATURE REVIEW INTEGRATING ESG AND GOVERNANCE - Hasibuan, Renika; Sambas Ade Kesuma; Iskandar Muda (Accounting Profession Journal (APAJI), 2025)
This study aims to systematically review the literature on financial performance in the digital era by integrating Environmental, Social, and Governance (ESG) factors and corporate governance. Employing a Systematic Literature Review (SLR) methodology based on the PRISMA framework, this review analyzes 71 selected articles published between 2018 and 2025. The findings reveal a complex interaction between digitalization, ESG practices, and governance mechanisms in shaping corporate financial outcomes. The study contributes by identifying key themes, research gaps, and providing future research directions for achieving business sustainability and long-term value creation.